OPTIMIZATION OF COMPRESSOR PERFORMANCE ON THE SHIP KM. PUSRI INDONESIA - Sidharta, Driaskoro Budi; Amrillah, Muhamad Fahmi; Sari, Rhegina Marlova (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2025)
The KM. Pusri Indonesia is a bulk carrier owned by PT. Pupuk Indonesia Logistik, specifically designed to distribute fertilizer from producers to various locations throughout Indonesia. Based on the survey results, this study aims to identify factors causing performance decline and implement optimization measures for the compressor. Air compressors play a vital role in providing pressurized air to various ship machinery systems, so decreased performance can hamper operations. The results of this study indicate that the air cylinder filling time increased from the standard specification of 2.4 to 5 minutes to 7.4 to 10 minutes. The main contributing factors are piston ring wear, scale buildup on the low and high pressure valves, and leaks in the cooling pipes. To address this issue, optimization steps that can be taken include replacing worn piston rings, cleaning scale on the valves, and welding leaking cooling pipes. After corrective action, the filling time returned to the normal range of 2.8 to 4.9 minutes. This study emphasizes the importance of compressor maintenance in accordance with the manual and recording maintenance results for evaluation purposes.